CIVIC EDUCATION IN PRIMARY SCHOOLS AS A MEANS OF SHAPING SOCIAL ATTITUDES AND ACTIVE ROLES IN NATIONAL DEVELOPMENT: A LITERATURE REVIEW - Marzuki Marzuki; Al-Amin (Adisam Publisher, 2025)
Civic education in primary schools is an important instrument in shaping the character of the nation's children to have a national perspective, positive social behaviour, and be ready to contribute to the development of the country. This study uses a literature review to examine the role of civic education in shaping social attitudes and fostering active participation among students from an early age. The results of the literature review show that PKn is effective in instilling the values of tolerance, mutual cooperation, solidarity, responsibility, and legal awareness, which are the foundations of social life. In addition, PKn is able to encourage student involvement in various social activities and simple democratic activities, which then become initial training in actively participating in the development of the nation and state. With a participatory learning approach, teacher role models, and integration with the environment and family, PKn can make a real contribution to creating a young generation with social character, who are caring and have an active role in sustainable national development.